2009
DOI: 10.3174/ajnr.a1639
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Functional Outcome in Acute Cerebral Hemorrhage Using Diffusion Tensor Imaging at 3T: A Prospective Study

Abstract: BACKGROUND AND PURPOSE:Early evaluation of the pyramidal tract is a prerequisite in patients with intracerebral hemorrhage (ICH) in order to decide the optimal treatment or to assess appropriate rehabilitation. The aim of this study was to evaluate and predict the neuromotor and functional outcome of an ICH by using diffusion tensor imaging (DTI) in the acute phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 30 publications
7
69
0
1
Order By: Relevance
“…The timing of the MRI being performed and clinical outcome evaluation are comparable with those of previously published reports, but we were able to recruit more cases than previous studies. 9,10,16 In addition, this is the first report to evaluate the relationship between the FA ratio in four different areas along the CST and motor outcomes after ICH, and the results may imply the value of microstructural change over the CST. However, further investigations are necessary to clarify the fibre change in an injured CST after ICH.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The timing of the MRI being performed and clinical outcome evaluation are comparable with those of previously published reports, but we were able to recruit more cases than previous studies. 9,10,16 In addition, this is the first report to evaluate the relationship between the FA ratio in four different areas along the CST and motor outcomes after ICH, and the results may imply the value of microstructural change over the CST. However, further investigations are necessary to clarify the fibre change in an injured CST after ICH.…”
Section: Discussionmentioning
confidence: 88%
“…[13][14][15] Most previous studies have used only the cerebral peduncle as the ROI for FA and ADC measurements to predict motor outcomes. 9,10,16 Our study is unique in that we assessed four sites along the CST, to measure DTI indices including the corona radiata, perihaematomal oedema area, cerebral peduncle and pons. Different from previous studies, this showed that injured CST could change during the motor recovery stage among patients with ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kusano et al 29 reported that FA indexes measured in the cerebral peduncles within 2 days after intracerebral hemorrhage onset may predict functional motor outcome. In this study, a region of interestϪbased analysis of the FA of the CST in the cerebral peduncles showed that FA measured in the affected side decreased by 11% compared with the unaffected cerebral peduncle.…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of the cause of motor weakness is essential for prognosis and for adoption of scientific strategies for successful rehabilitation [22][23][24][25][26]. Recovery following a stroke is typically classified into neurological recovery and functional recovery; functional recovery is influenced by the external environment, continuity of rehabilitation, and motivation, whereas neurological recovery varies according to stroke pathogenesis and lesion site [27].…”
Section: Correlation Between Brain Lesion and Motor Recoverymentioning
confidence: 99%